Botany, sexuality and women's writing, 17601830;from modest shoot to forward plant. (MANCHESTER UNIV Press, 2017)
In this fascinating study, Samantha George explores the cultivation of the female mind and the feminised discourse of botanical literature in eighteenth-century Britain. In particular, she discusses British women's engagement with the Swedish botanist, Carl Linnaeus, and his unsettling discovery of plant sexuality. Previously ignored primary texts of an extraordinary nature are rescued from obscurity and assigned a proper place in the histories of science, eighteenth-century literature, and women's writing. The result is groundbreaking: the author explores nationality and sexuality debates in r.
Keywords: Linné, Carl von, -- 1707-1778 -- Influence.; Linné, Carl von, -- 1707-1778; Linné, Carl von, -- 1707-1778 -- influenser.; Linné, Carl von (Biologe, -- 1707-1778); Botanical literature -- Women authors -- History -- 18th century.; Botany in literature -- History -- 18th century.; Women botanists -- History -- 18th century.; Plants, Sex in -- Early works to 1800.; Botanique dans la littérature -- Histoire -- 18e siècle.; Femmes botanistes -- Histoire -- 18e siècle.; Plantes -- Sexualité -- Ouvrages avant 1800.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Botany in literature; Influence (Literary, artistic, etc.); Plants, Sex in; Women botanists; Pflanzen; Geschlechtliche Fortpflanzung; Rezeption; Frauenliteratur; Großbritannien; Kvinnliga botaniker -- historia -- 1700-talet -- 1800-talet.; Engelsk litteratur -- kvinnliga författare -- historia -- 1700-talet -- 1800-talet.; Botanik i litteraturen.; 1700-1799; Early works; History